ANALISIS PERKEMBANGAN SOSIAL ANAK AUTISME (ANAK BERKEBUTUHAN KHUSUS) DI LINGKUNGAN KELUARGA - Delita Wulan cahyani; Yahdinil Firda Nadira (STKIP Subang, 2025)
Children with autism are individuals who experience developmental disorders in the brain, which affect social abilities, both verbal and non-verbal communication, imagination, flexibility, cognition, and focus. This condition makes children with autism have difficulty interacting socially and communicating with other people, so they tend to be more immersed in their own world and show certain behaviors in response to the environment around them. Symptoms of autism include difficulty making social connections, unusual communication patterns, and restricted, repetitive, and consistent behavior. Children with autism often show delays in language skills and in social interactions, as well as in playing in symbolic or imaginative ways. In general, children with autism show signs such as lack of eye contact, inadequate response to the surrounding environment, difficulty communicating, repetitive behavior, and disturbances in sensory processing. Support from parents, teachers and the environment is very important in creating a comfortable atmosphere for autistic children so that they can grow well